Avaliação de política pública de educação especial na Escola Municipal Professora Maria do Socorro Viana Freitas - Bezerra, Michella Daustria de Queiroz (2024)
This research aims to evaluate the experience and results of using the Multifunctional Resource Room (SRM), in view of its contribution to the development of students served by the Specialized Educational Service (AEE), based on the practice experienced at the EMEIEF Prof school.ª. Maria do Socorro Viana Freitas, from the municipal education network in the city of Maracanaú-CE. The relevance of this evaluative research lies in the search to bring more clarity to the topic, considering that evaluating the implementation of a public policy implemented with the aim of combating inequalities, as is the case of the public policies analyzed here, is a complex and controversial subject, that provokes and tensions discussions, projects dissonances, contradictions and paradoxes, consensus and dissent. The need for effective inclusion of people with disabilities in the school space has been discussed for some time, that is, through inclusive education, so that these citizens can become empowered and occupy a place of belonging in society. Given this context, we consider it pertinent to raise a discussion about the concepts of Citizenship; Right to Education for people with disabilities, to support the assessment contained therein. Furthermore, the study highlights, in addition to other extremely important documents, the National Policy on Special Education from the Perspective of Inclusive Education, from 2008, which brought with it the establishment of Specialized Educational Assistance – the AEE. It is a complementary and supplementary modality to regular education, aimed at students with disabilities, global developmental disorders and high abilities/giftedness. It is offered individually or in small groups, according to the specific demands of each student, and is carried out by specialized teachers, who have training in special education or related areas, in the school's SRMs. Regarding the methodology, it is a qualitative and quantitative research, which in turn, allows the study to integrate the description, classification and interpretation of empirical information with the analysis of statistics and numerical data. Furthermore, the research uses bibliographic and documentary research as methodological procedures and collects data through the application of semi-structured questionnaires. Anticipating some results, it was possible to identify the importance of Specialized Educational Assistance (AEE) and Multifunctional Resource Rooms (SRM) in promoting the educational inclusion of students with special needs in public schools. It was observed that AEE and SRM play a crucial role in offering specialized support, adapted to the individual needs of each student, contributing to their full academic and social development. However, significant challenges were also identified, such as the lack of adequate training for professionals, the scarcity of financial resources and the need for more effective public policies to guarantee equitable access to quality educational services. In this sense, the research highlighted the importance of investing in specialized teacher training, inclusive policies and adequate resources to promote a truly inclusive and accessible education for all students, regardless of their needs or socioeconomic conditions, also guaranteeing the full exercise of citizenship and the access to what is a right for everyone: Quality education.